Health status, ability, and motivation infl uenced district hospital nurse performance (Medical Journal of Indonesia, 2009)
Aim To investigate the influence of health status, ability and motivation of nurses' performances in a district hospital. Methods A survey was conducted during May 2009 in a district hospital in West Java, Indonesia. Nurses in the inpatient and outpatient unit and fulfilled inclusion and exclusion criteria were randomly chosen as the unit of analysis. A questionnaire of 18-23 questions was used to measure the indicator of the four variables. The path analysis was performed using multiple regressions for calculating ß as the value of path coefficient between variables, p value and R2. Goodness of fit test was used to calculated Q and W coefficient. Results Test was performed on 125 of 493 nurses with exogenous (independent) and endogenous (intermediate or dependent) variables in the model proposed. The p-value was > 0.05, indicating that the characteristics variation of the subjects did not affect the answers on the endogenous and exogenous variables. The health status, ability, motivation and performance variables showed normal and homogenous distribution. Line equation between variables showed linear relation with p<0.05. Simple correlation score between variables was 0.376 to 0.833. Ability was the biggest variable that influences nurses' performance (44.8%), followed by motivation (33.9%) and health status (21.8%). The influences of the three exogenous variables to nurses' performance were 76.2% and 23.8% which was influenced by other variables. Conclusion Nurses' health status, ability, and motivation influenced their performance. Therefore, these variables can be considered for an intervention to improve the nurses' performance. (Med J Indones 2009; 18: 283-9)